Implikasi Pandemi Covid-19 Terhadap Penanganan Tindak Pidana Korupsi Oleh Kejaksaan - Munirah, Intan; Awaljon, M Gempa (Prodi Ilmu Hukum, Universitas Teuku Umar, 2023)
The crime of corruption is included in a special crime, regulated by a special law, namely Law Number 31 of 1999 as amended by Law Number 20 of 2001. However, based on data on the performance achievements of the Attorney General's Office of the Republic of Indonesia in December 2020, it is explained that the process of handling corruption crimes has not yet reached the performance target at each stage of handling corruption cases, besides that the level of public satisfaction with the performance of the Attorney General is ranked fourth. It is important to study the obstacles and barriers. Obstacles in the handling of corruption cases that occur at the investigation stage, the number of personnel is not balanced with the high workload so that additional professional personnel are needed. obstacles in the process of handling corruption crimes due to the Covid-19 pandemic outbreak which hindered the process so that it was not resolved on time.